Schools’ air quality monitoring for health and education: Methods and protocols of the SAMHE initiative and project - Lia Chatzidiakou; Rhys Archer; Victoria Beale; Sam Bland; Holly Carter; Claudia Castro-Faccetti; Hannah Edwards; Joshua Finneran; Sarkawt Hama; Roderic L. Jones; Prashant Kumar; Paul F. Linden; et al. (Developments in the Built Environment, 2023)
Background: Children spend significant amounts of time at school, making the school environment a potentially important contributor to air quality exposure. Aim: The SAMHE initiative has a dual aim: 1) to develop and test a bespoke citizen science framework for collecting environment and indoor air quality data in classrooms, alongside contextual data capable of enriching analysis, at an unprecedented scale; and, 2) to simultaneously use these methods to raise awareness among communities regarding their exposure to air pollution in the school environment. Methodology: To achieve this dual aim, the SAMHE project was initiated to deploy more than 2 000 low-cost indoor air quality monitors in school classrooms. A Web App has been co-designed with schools to support collecting a large comprehensive dataset (including school buildings characteristics, operation, and behavioural patterns) and to enable students and teachers to interact with the data gathered in their school. Results and outlook: We present the design of the interface and visuals that have been co-designed with 20+ schools and tested with 120+ schools. Within one week of the SAMHE launch week, 537 schools had registered to join the project, and at the time of writing (just seven weeks later) this number had grown to around 800 schools. This highlights the potential for this novel initiative to provide a step-change in the way that indoor air quality datasets are gathered at a national and, potentially, international level while simultaneously enabling schools to better manage their indoor environment and empowering students and teachers to reduce their environmental health risks.